Effect of environmental and cultural factors during growth of seed potato (Solanum tuberosum) crop on subsequent performance of progeny tubers as seed - EZEKIEL, R (The Indian Journal of Agricultural Sciences, 2013)
:The effect or different envionmental and cultural factors during the production or seed potato (Solanum tuberosumL.) on the yield potential of progeny tubers was studied in 5 field trials conducted for 5 years. Higher temperature during the growth of seed crop caused 15 -19% reduction in the yielding ability of progeny tubers. Different daylengths during seed crop growth had no effect on the yield potential of progeny tubers. Seed produced at higher altitude (at Kufri) gave higher yield than that prouuced at lower altitude (at Modipuram), This difference in yield may he due to difference in the physiological age or seed tubers at the time of planting rather than due to the altitde, The level of N fertilizer applied to the seed crop did not affeet the yield potential of progeny tubers, nor did drought. The temperature during the growth of seed crop and the physiological age of the seed tubers were found the dominant Hlctors that affect the performance of progeny seed tubers.